2015
DOI: 10.1186/s12960-015-0073-8
|View full text |Cite
|
Sign up to set email alerts
|

Human resources for primary health care in sub-Saharan Africa: progress or stagnation?

Abstract: BackgroundThe World Health Organization defines a “critical shortage” of health workers as being fewer than 2.28 health workers per 1000 population and failing to attain 80% coverage for deliveries by skilled birth attendants. We aimed to quantify the number of health workers in five African countries and the proportion of these currently working in primary health care facilities, to compare this to estimates of numbers needed and to assess how the situation has changed in recent years.MethodsThis study is a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
117
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(125 citation statements)
references
References 16 publications
5
117
0
3
Order By: Relevance
“…As such, not only do insufficient and sub-optimally allocated resources attend the health needs of populations with some of the more complex health challenges in the world, but people's trust in health systems is shaken by frequent stock-outs of essential medicines [68][69][70] and overstretched health personnel, particularly in low-level health facilities and poor areas. 71,72 People's access to health services is in many cases is further obstructed by long distances, high travel costs, high out-of-pocket (OOP) payments, cultural beliefs, and queues. Barriers to access have been primarily researched for rural settings, but are equally relevant for those hard to reach in urban settings.…”
Section: Health Systems In Sub-saharan Africamentioning
confidence: 99%
See 1 more Smart Citation
“…As such, not only do insufficient and sub-optimally allocated resources attend the health needs of populations with some of the more complex health challenges in the world, but people's trust in health systems is shaken by frequent stock-outs of essential medicines [68][69][70] and overstretched health personnel, particularly in low-level health facilities and poor areas. 71,72 People's access to health services is in many cases is further obstructed by long distances, high travel costs, high out-of-pocket (OOP) payments, cultural beliefs, and queues. Barriers to access have been primarily researched for rural settings, but are equally relevant for those hard to reach in urban settings.…”
Section: Health Systems In Sub-saharan Africamentioning
confidence: 99%
“…71,277 In some countries it will be decades before the minimum thresholds are reached. Therefore, much more investment is needed in pre-service education and training to increase the supply of all types of health workers, including less familiar cadres that are relatively quick to train and able to meet local health needs.…”
Section: Figure 14: Where Are Doctors 5 Years After Graduating From Amentioning
confidence: 99%
“…This contributes to the limited evidence base on the equitable distribution of human resources at the facility level [64], and it is the second study, to our knowledge, to look at equity in the distribution of drugs, medical equipment and supplies from the district level down to the facility level [55]. …”
Section: Discussionmentioning
confidence: 99%
“…To date, benefit incidence studies have generally found that the distribution of government health budgets tends to be pro-rich, with the better-off having better access to publicly-funded health services [55]. This is partly due to the concentration of health care inputs (funds, staff, medical supplies, drugs and equipment) at facilities located in urban areas that are more accessible to wealthier groups [9, 64]. Similarly, a study in Tanzania found that 20% of the population with the fewest health workers per capita had only 8% of health workers, compared to 46% in the 20% of the population with the most health workers [39].…”
Section: Introductionmentioning
confidence: 99%
“…Ghana's doctor and nurse population ratio is 1:10,452 for doctors and 1:1,251 for nurses, as per the 2012 annual report on the Ghana Shared Growth and Development Agenda [6]. There is no agreed international standard for overall staffing of primary health care [7]. However, in 2006 the World Health Organization (WHO) defined countries as having a critical shortage of health workers if they had fewer than 2.28 doctors, nurses, and midwives per 1,000 population and if they failed to reach the target of 80% of deliveries being attended by a skilled birth attendant [8].…”
Section: Introductionmentioning
confidence: 99%